Editorials - Hayes, Grahame (PINS-Psychology in Society, 2026)
PINS launched itself, in September 1983, with the following editorial briefing: "Psychology in society is a journal which aims to critically explore and present ideas on the nature of psychology in capitalist society. There is a special emphasis on the theory and practice of psychology in the South African context". This was followed by a 20 page editorial article outlining the context of the formation of this new journal and the role it saw itself fulfilling. This briefing was minimally, yet significantly, altered two years later in PINS 3 (1985), by the inclusion of the term "apartheid" as a central defining feature of our society, and to register psychology’s complicity with this form of racial oppression. The editorial masthead now read: "Psychology in society is a journal which aims to critically explore and present ideas on the nature of psychology in apartheid and capitalist society. There is a special emphasis on the theory and practice of psychology in the South African context".